Diagnosis and comprehensive treatment for patients with Amelogenesis Imperfecta. Case report - María del Carmen López Jordi; Esther Szwarc (Asociación Latinoamericana de Odontopediatría, 2019)
Amelogenesis Imperfecta is a diverse group of hereditary and heterogeneous enamel defects, due to alterations in the formation of dental enamel in quality and/or quantity. Diagnosis is based on clinical and radiological findings, family history, family tree, and genetic diagnosis when it is possible. It is characterized by a wide range of clinical presentations in both dentitions. This condition has a high impact on children and adolescents, generates a very disadvantageous social performance since aesthetic problems and dysfunction limit their quality of life. Comprehensive care becomes an essential aspect and it demands a close and necessary professional, patient and family interaction, which must be established early and in an interdisciplinary way. Objective: We present a patient with Amelogenesis Imperfecta, 11 years old, with a clinical and radiographic diagnosis of hypoplastic type, based on her family history. The treatment integrated several stages: use of remineralizing agents in order to restore Latinoamericanadental tissues, orthodontics to create space for the eruption of the retained canine (13), and the alignment of upper dental arch, and rehabilitation with composite resins and metal crowns fenestrated in occlusal. Conclusion: The five year follow- up, with a very positive attitude of the patient toward the maintenance of her health, suggests that in adolescence, a healthy smile is important in the development of self-esteem and interpersonal relationships.